Bioanalysis: Enzymatic Growth of Metal and Semiconductor Nanoparticles in Bioanalysis (Part. Part. Syst. Charact. 1/2014). (January 2014) - Pavlov, Valeri
<x xml:space="preserve">Abstract</x> Fluorescent semiconductor and metal nanoparticles are ubiquitously used in bioanalysis to highlight the presence of target analytes including enzymes, antibodies, etc. In his Review on page 36, Valery Pavlov describes how biosensing takes advantage of the synthesis of nanoparticles in situ triggered by a recognition event. The enzymatic synthesis of NPs in situ allows significant improvement of the signal‐to‐noise ratio, which significantly improves the sensitivity of analytical assays. Enzymes generate compounds that influence formation of metal and semiconductor nanoparticles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>